Profitability trends in the era of financialization: Notes on the U.S. economy. Issue 1 (3rd April 2019) - Lapavitsas, Costas; Mendieta-Muñoz, Ivan
Abstract: This article considers the evolution of financialization in the U.S. economy by examining the profitability and the volume of profits of the financial sector relative to general profitability and total profits in the economy. It is shown that financial profitability rose strongly from the early 1980s to the early 2000s. Similarly, the volume of financial profits reached extraordinary levels in the early 2000s. These phenomena occurred while interest rates and the net interest margin of banks were on a downward trend and, broadly speaking, reflect financial expropriation in the U.S. economy. The great crisis of 2007–2009 has acted as a threshold point beyond which both the profitability and the volume of profits of the financial sector have not recovered to previous levels. It is possible, but not certain, that a rebalancing of the productive and the financial sectors is under way in the financialized U.S. economy.